2002
DOI: 10.1089/08892220260190290
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper on Therapeutic Drug Monitoring of Antiretroviral Agents

Abstract: Monitoring drug concentrations in humans to optimize efficacy and reduce toxicity is not a new concept in clinical pharmacology. It has been successfully applied to many different classes of drugs. As a result of considerable concentration and response data, the concept of therapeutic drug monitoring (TDM) has been expanded to certain antiretroviral compounds. In particular, protease inhibitors and nonnucleoside reverse transcriptase inhibitors may be viable candidates for TDM, and limited clinical trial data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 22 publications
2
56
0
1
Order By: Relevance
“…The AUCs were well in excess of the targeted value in all subjects. In addition, the C 12 s were also above a suggested acceptable lower limit of 50 ng/ml, based on prior pharmacodynamic analyses (7), and were within or above the range of 100 to 250 ng/ml established by a consensus panel (3). Our pharmacokinetic results suggest that the level of SQV exposure during the postpartum period is increased relative to that in nonpregnant individuals (12).…”
Section: Discussionsupporting
confidence: 65%
“…The AUCs were well in excess of the targeted value in all subjects. In addition, the C 12 s were also above a suggested acceptable lower limit of 50 ng/ml, based on prior pharmacodynamic analyses (7), and were within or above the range of 100 to 250 ng/ml established by a consensus panel (3). Our pharmacokinetic results suggest that the level of SQV exposure during the postpartum period is increased relative to that in nonpregnant individuals (12).…”
Section: Discussionsupporting
confidence: 65%
“…Numerous papers have suggested children as a target population for antiretrovirals [6][7][8]. For abacavir, a pharmacokineticpharmacodynamic study in adults demonstrated that the endpoint for efficacy, as indicated by the change from baseline in viral load (plasma HIV-1 RNA) and rise in CD4+ T cell count, was significantly correlated with area under the concentration-time curve (AUC) [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, although TDM has been incorporated into anti-HIV treatment guidelines (3,4,(6)(7)(8), prospective randomized clinical trials assessing the usefulness of this strategy have shown contradictory results (3,9). Moreover, the determination of anti-HIV drug concentration in other biological samples, such as peripheral blood mononuclear cells, allows drug monitoring at their pharmacological action sites (10).…”
Section: Introductionmentioning
confidence: 99%